Implications of 3-methylhistidine titres of actin and myosin in determining meat protein - Johnson, Stuart Keith (1988)
The widespread use of nan4meat protein in meat products necessitates a method for the robust, unequivocal quantification of meat in foods. Protein-bound levels of the co- or post-translationally modified amino acid, 3- methylhistidine, virtually unique to the myofibrillar proteins actin and myosin, have previously been proposed as such an index, determination being by high-performance liquid chromatography of acid stable fluorescamine derivatives. Although robust to the severest processing conditions, variations in the titres of 3-methylhistidine in certain manufacturing cuts have been reported. The present study has revealed that such variations can be attributed to the low level of 3-methylhistidine in the myosin of muscles high in "red" (oxidative) fibres, such as ruminant Masseter; constant levels of 3-methylhistidine being found in all actins investigated. Methods for the determination of actin-bound 3- methylhistidine have therefore been developed. Electrophoretic separation of actin with 3-methylhistidine determination of the resulting actin band was found to be only semi-quantitative. The isolation of actin by conventional SOS-gel filtration was time consuming and resulted in low yields of 3-methylhistidine. SDSgel filtration using the Pharrnacia fast protein liquid chromatography (FPLC) system, allowed rapid, reproducible and quantitative isolation of actin-bound 3-methlhistidine. Using too latter method, constant levels of actin-bound 3-methylhistidine have been found for all muscles investigated. A new unequivocal definition of "meat", is proposed as that which has an actinbound 3-methylhistidine content of 3mg/g non-connective tissue nitrogen. This is expected to be robust to all but the severest processing conditions. Such an index, based on connective tissue free units, requires the accurate determination of hydroxyproline, for which a sensitive method using gas chromatography-mass spectrometry has been developed. The use of an assumed average "factor" for the conversion of hydroxyproline to connective tissue appears valid, since the hydroxyproline contents of the connective tissue of all muscles investigated were similar.